The legal regulation in Ukraine victims of domestic violence medical examination and providing them medical assistance - Anishchenko, M. A.; Muntian, L.; Mazur, I.; Hamburh, L. S.; Samko, A. V.; Аніщенко, Михайло Анатолійович; Мунтян, Л.; Мазур, І.; Гамбург, Леонід Самойлович; Самко, Анатолій Васильович (My University, 2021)
The article explores the legal regulation of the system of medical examination and medical assistance in relation to victims of domestic violence in Ukraine, taking into account the priority of international law and the signing by representatives of Ukraine on November 7, 2011 of the Istanbul Convention of May 11, 2011, (but until now time not ratified by the Verkhovna Rada). The latest legislation of Ukraine on prevention and counteraction domestic violence defines the list of subjects authorized to carry out the relevant measures, including bodies, healthcare establishments and institutions, and regulates their powers in this area. By the decrees of the President of Ukraine, Resolutions of the Cabinet of Ministers of Ukraine and orders of the Ministry of Health of Ukraine, the procedure and mechanism for conducting medical examinations of victims of domestic violence and gender-based violence and documenting its results, providing them with medical assistance to ensure an intersectoral approach to countering such violence and overcoming it, and promoting the realization of the rights of victims of him. The legal regulation in Ukraine medical examination of victims of domestic violence and the provision of medical assistance to them, the main problems are identified and ways to solve them are proposed.
Keywords: domestic violence; victims of domestic violence; medical examination; medical assistance